Quality and microbiological analysis of Rosmarinus officinalis (alecrim) (Research, Society and Development, 2022)
Rosmarinus officinalis L. is a plant grown in several regions, popularly known as rosemary, it has different therapeutic properties due to its chemical diversity associated with bioactive molecules and its phenolic compounds, providing certain curative and/or prophylactic effects such as antioxidant, anti-inflammatory, calming action. , antimicrobial and even hepatoprotective given the above, this research aims to make a quality and microbiological analysis of the processed and dehydrated herb (rosemary) obtained at the ver-o-peso market, city of Belém-PA, through the qualitative method, determination of foreign material, loss of desiccation, microscopic and phytochemical analysis based on the Brazilian Pharmacopeia. The results of organoleptic analysis and foreign material showed characteristic of rosemary and small contaminants such as stones and hair, microscopic analysis identified the presence of microorganisms with morphological characteristics suggestive of fusarium sp, iodamoeba cyst and bacteria, phytochemical analyzes were positive for flavonoids, tannins and saponins, the benefits of using rosemary are still investigated, however research on quality is still little explored despite its market potential.